Macmillan encyclopedia of the environment. Volume 4 - Black, Matthew, naturalist; Haley, Richard; Kellert, Stephen R. (New York : Macmillan Library Reference USA, 1997)
Provides basic information about such topics as minerals, energy resources, pollution, soils and erosion, wildlife and extinction, agriculture, the ocean, wilderness, hazardous wastes, population, environmental laws, ecology, and evolution.
8.1.
8.1
5-8
Keywords: Environmental sciences -- Encyclopedias, Juvenile; Ecology -- Encyclopedias; Environmental protection -- Encyclopedias; Ecology -- Encyclopedias; Environmental protection -- Encyclopedias